Serum levels of inflammatory cytokines in Rift Valley fever patients are indicative of severe disease. Issue 1 (December 2015) - Jansen van Vuren, Petrus; Shalekoff, Sharon; Grobbelaar, Antoinette; Archer, Brett; Thomas, Juno; Tiemessen, Caroline; Paweska, Janusz
Abstract Background Rift Valley fever (RVF) is a mosquito-borne viral zoonosis affecting domestic and wild ruminants, camels and humans. Outbreaks of RVF are characterized by a sudden onset of abortions and high mortality amongst domestic ruminants. Humans develop disease ranging from a mild flu-like illness to more severe complications including hemorrhagic syndrome, ocular and neurological lesions and death. During the RVF outbreak in South Africa in 2010/11, a total of 278 human cases were laboratory confirmed, including 25 deaths. The role of the host inflammatory response to RVF pathogenesis is not completely understood. Methods Virus load in serum from human fatal and non-fatal cases was determined by standard tissue culture infective dose 50 (TCID50 ) titration on Vero cells. Patient serum concentration of chemokines and cytokines involved in inflammatory responses (IL-8, RANTES, CXCL9, MCP-1, IP-10, IL-1β, IL-6, IL-10, TNF and IL-12p70) was determined using cytometric bead assays and flow cytometry. Results Fatal cases had a 1-log10 higher TCID50 /ml serum concentration of RVF virus (RVFV) than survivors (p < 0.05). There were no significant sequence differences between isolates recovered from fatal and non-fatal cases. Chemokines and pro- and anti-inflammatory cytokines were detected at significantly increased (IL-8, CXCL9, MCP-1, IP-10, IL-10) or decreased (RANTES) levels when comparing fatal cases to infected survivors and uninfected controls, or when comparing combined infected patients to uninfected controls. Conclusions The results suggest that regulation of the host inflammatory responses plays an important role in the outcome of RVFV infection in humans. Dysregulation of the inflammatory response contributes to a fatal outcome. The cytokines and chemokines identified in this study that correlate with fatal outcomes warrant further investigation as markers for disease severity.